Multi-gene phylogenetic and taxonomic contributions to Xylaria (Ascomycota) associated with fallen fruits from China - Zhu, An-Hong; Song, Zi-Kun; Wang, Jun-Fang; Guan, Hao-Wen; Qu, Zhi; Ma, Hai-Xia (MycoKeys (Sofia, Bulgaria), 2024)
Morphological and phylogenetic analyses on samples of Xylaria species associated with fallen fruits from China were carried out, and two new species were described, namely X. aleuriticola and X. microcarpa . Xylaria aleuriticola is found on fallen fruits of Aleurites moluccana , and characterized by stromata dichotomously branched several times with long acute sterile apices, fertile parts roughened with perithecia and tomentose, and ellipsoid to fusiform ascospores. Xylaria microcarpa differs in its very small stromata with dark brown tomentum, light brown ascospores with an inconspicuous straight germ slit, and grows on leguminous pods. The differences between the new species and morphologically similar species are discussed. Phylogenetic analyses on ITS-RPB2-TUB sequences confirmed that the two species are clearly separated from other species of the genus Xylaria . Xylaria liquidambaris is reported as a new record from China. A key to the Xylaria species associated with fallen fruits and seeds reported from China is provided to facilitate future studies of the genus.